Kesan Penggunaan Peta Konsep dan Pembelajaran Koperatif terhadap prestasi pelajar dalam mata pelajaran sejarah tingkatan empat - Mohan Rathakrishnan; Balan Rathakrishnan (Faculty of Management, Universiti Teknologi Malaysia, 2005)
This article attempts to examine the effectiveness of the use of concept map cognitive strategies and cooperative learning to improve comprehension, short-term knowledge, and ability to solve a given problem based on the topics taught in the form of essay questions at the end of the lesson or test for Form Four History subject. This study also aims to see the difference in performance between male and female students who use concept map cognitive strategies and cooperative learning than male and female students who do not use cooperative learning. A total of 60 students from secondary schools in Penang were taken as a sample. This study used a quasi-experiment with a 2x2 factorial design involving t-test at a 0.05 significance level. The results showed that students who learn to use concept maps learning strategies and cooperative approach can improve performance achievement in the subject of history. Students not only can improve the understanding of the topic being taught, but also can use the new knowledge gained from cooperative learning to solve problems with more confidence. Therefore, learning using concept maps and cooperative strategy is proposed to be practiced in the teaching and learning of History subject in form 4.